2008
DOI: 10.1021/jp7108434
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Proton Transport in the Short-Side-Chain Perfluorosulfonic Acid Ionomer

Abstract: An explanation for the superior proton conductivity of low equivalent weight (EW) short-side-chain (SSC) perfluorosulfonic acid membranes is pursued through the determination of hydrated morphology and hydronium ion diffusion coefficients using classical molecular dynamics (MD) simulations. A unique force field set for the SSC ionomer was derived from torsion profiles determined from ab initio electronic structure calculations of an oligomeric fragment consisting of two side chains. MD simulations were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 41 publications
8
93
1
Order By: Relevance
“…Ab initio molecular dynamics (AIMD) calculations have also been performed to investigate proton transfer and dynamics for model systems exhibiting a high density of perfluorinated sulfonic acid groups (29)(30)(31)(32). On a larger scale are the classical molecular dynamics (MD) simulations on structural correlations and transport properties of PEMs (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). These include empirical valence bond (EVB) models of the solvation and transport of hydrated protons (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio molecular dynamics (AIMD) calculations have also been performed to investigate proton transfer and dynamics for model systems exhibiting a high density of perfluorinated sulfonic acid groups (29)(30)(31)(32). On a larger scale are the classical molecular dynamics (MD) simulations on structural correlations and transport properties of PEMs (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). These include empirical valence bond (EVB) models of the solvation and transport of hydrated protons (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…11 SSC ionomers have also been the subject of several theoretical and molecular-level modelling studies, [12][13][14][15][16][17][18] from which, the effect of backbone flexibility, length of side chain, IEC, and molecular weight on proton transport processes, under varying levels of hydration, has been revealed.…”
mentioning
confidence: 99%
“…Much larger water uptakes were observed compared to low IEC Hyflon membranes, and molecular modelling studies of proton transport in SSC PFSA membranes (IEC = 1.72 mmol g À1 ) revealed that the calculated hydronium ion diffusion coefficient increased with water content. 18 Noteworthy, the studies referredt oa b o v ed e s c r i b ep r o p e r t i e s of SSC PFSA ionomer membranes prepared by extrusion; the properties of solution-cast SSC PFSA membranes is sparse, despite the significant effect processing conditions exert on membrane properties, as clearly demonstrated for LSC PFSA ionomer membranes. 1 Recently, we reported fuel cell performances of membrane-electrode-assemblies using high IEC SSC ionomer (1.3, 1.4, 1.5 mmol g À1 ) as the proton conducting medium dispersed in the catalyst layer.…”
mentioning
confidence: 99%
“…In addition, classical MD simulations of a SSC PFSA membrane of EW 580 showed that SSC PFSA membranes have a greater number of free hydronium ions at the same hydration level compared with the nafion [59]. This interestingly suggests that the complexity of proton conduction is one of the major determinants of the proton conductivity since, as mentioned previously, Kreuer et al [43] showed that the nafion has higher proton conductivity than the SCC PFSA membranes at low hydration level.…”
Section: Sourcementioning
confidence: 72%